Direct healthcare costs of glaucoma treatment. Issue 6 (16th April 2013) - Rahman, M Q; Beard, S M; Discombe, R; Sharma, R; Montgomery, D M I
Abstract : Aims: To report the complete lifetime direct healthcare costs of glaucoma treatment in a database of 1136 patients attending the Glaucoma Clinic at Glasgow Royal Infirmary, Glasgow, UK. Method: The database was interrogated to identify all patients who had initiated treatment at the Glaucoma Clinic at Glasgow Royal Infirmary, and who had subsequently died of natural causes. The healthcare resource use based cost assessment was based on two aspects of the direct National Health Service cost: drug costs (prescribed medications) and non-drug costs (inpatient or outpatient/and surgical or procedure costs). Results: 106 patients (53 men, 53 women) were identified for whom there were lifetime treatment data. The mean lifespan of the patients was 80.5 years, and the mean number of years attending the glaucoma clinic was 7.05 years (range 1–22 years). The mean cost of glaucoma treatment over the lifetime of the patients was £3001, with an annual mean cost per patient of £475. Non-drug and drug costs made up 66% and 34% respectively, of the lifetime costs. Conclusions: This is the only study to directly assess the lifetime treatment costs of glaucoma. Awareness of the costs of glaucoma treatment may be of increased importance in these financially challenging times.